Assessing Adventitious Matches of Non-Donors Related to True Contributors - Kaitlin Huffman; Lilliana Moreno (Biomolecules)
Relatives share more DNA with one another than unrelated individuals. Therefore, there is an increased risk of close relatives (e.g., siblings or parents and children of true donors) adventitiously ‘matching’ DNA mixtures to which they are not a true contributor. One such method of addressing relatives is to utilize alternative propositions within probabilistic genotyping software (e.g., STRmixTM). As the number of related individuals within a mixture increases, so does the potential for adventitious matches of related non-donors to the mixture due to increased allele sharing. The extent to which siblings and parents/children of true donors result in adventitious matches to mixtures in which they are non-donors is presented as well as the impact of overestimating the number of contributors (NOC) when related donors are in question.